Automated conserved non-coding sequence (CNS) discovery reveals differences in gene content and promoter evolution among grasses - Turco, Gina; Schnable, James C.; Pedersen, Brent; Freeling, Michael (Frontiers in Plant Science, 2013)
Conserved noncoding sequences (CNS) are islands of noncoding sequence that, like protein coding exons, show less divergence in sequence between related species than functionless DNA. Several of CNSs have been demonstrated experimentally to function as cis-regulatory regions. However, the specific functions of most CNSs remain unknown. Previous searchers for CNS in plants have either anchored on exons and only identified nearby sequences or required years of painstaking manual annotation. Here we present an open source tool that can accurately identify CNSs between any two related species with sequenced genomes, including both those immediately adjacent to exons and distal sequences separated by >12 KB of noncoding sequence. We have used this tool to characterize new motifs, associate CNSs with additional functions and identify previously undetected genes encoding RNA and protein in the genomes of five grass species. We provide a list of 15,363 orthologous CNSs conserved across all grasses tested. We were also able to identify regulatory sequences present in the common ancestor of grasses that have been lost in one or more extant grass lineages. Lists of orthologous gene pairs and associated CNSs are provided for reference inbred lines of arabidopsis, Japonica rice, foxtail millet, sorghum, brachypodium and maize.